Pengaruh Hybrid Work Implementation dan Kesejahteraan Karyawan Terhadap Produktivitas Karyawan di Era Pasca-Pandemi: (The Impact of Hybrid Work Implementation and Employee Well-being on Employee Productivity in the Post-Pandemic Era) - Ramayanto; Baiq Reinelda Tri Yunarni; Candra; Sulhan Hadi; Rahmad Hidayat; Saskia Anggun Khairunnisa; Nazilatus Syiam (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2026)
This study aims to analyze the influence of hybrid work implementation and employee well-being on employee productivity at Grab in the Bali–Nusa Tenggara (Nusra) region in the post-pandemic era. This study employs a quantitative approach using a correlational research design. The sample size was determined using Lemeshow’s formula, resulting in 70 respondents selected through purposive sampling. Data collection was conducted through observation, interviews, and a questionnaire using a Likert scale. Data analysis employed multiple linear regression using SPSS, preceded by validity, reliability, and classical assumption tests. The results indicate that the implementation of hybrid work has a positive and significant effect on employee productivity, with a coefficient of 0.338 and a p-value of 0.012 (<0.05). Additionally, employee well-being also has a positive and significant effect with a coefficient of 0.434 and a significance level of 0.000 (<0.05), and is the more dominant variable. Simultaneously, both independent variables have a significant effect on employee productivity with a calculated F-value of 14.926 and a significance level of 0.000 (<0.05). The coefficient of determination (R²) of 0.288 indicates that the variables of hybrid work implementation and employee well-being account for 28.8% of the variation in employee productivity, while the remainder is influenced by other variables outside the scope of this study. This study concludes that increases in employee productivity are not solely determined by the implementation of a hybrid work system but are also significantly influenced by the level of employee well-being.